ANALISIS POSISI TERAPEUTIK TERHADAP PARAMETER HEMODINAMIK DIRUANG CVCU RSUD Prof. Dr. H. ALOEI SABOE KOTA GORONTALO - Nur Azmi S. Suleman; Damansyaha Haslinda (Universitas Sam Ratulangi, 2023)
Introduction: Acute Decompensated Heart Failure is acute heart failure in which the heart fails to pump blood to meet the body's needs and enough oxygen in to maintain adequate circulation. Objective: this study aims to analyze the therapeutic position of hemodynamic parameters in patients with Acute Decompensated Heart Failure. Method: This research used a descriptive research method with case study approach. This study involved four patients who experienced Acute Decompensated Heart Failure in the CVCU ward of Prof. Aloei Saboe Hospital, the instrument used the Standard Operating Procedures regarding therapeutic positions and observation sheets. Results: the study showed that the four patients on average had diverse hemodynamic status, namely systole 110-140mmHg and Diastole 60-90mmHg, pulse 80-98x/min, respiration 28-32x/min, body temperature 36-36.6C, SPO2 90-97%, MAP before implementation 77 mmHg-107 mmHg and MAP after implementation between 93 mmHg-103 mmHg. Conclusion: This study concluded that the patient's hemodynamic status can increase patient comfort, maintain the airway so that the need og oxygen supply can be met. Keywords: Therapeutic Position; hemodynamic parameters; ADHF